The treatment effect of rehabilitation gymnastics on postoperative rehabilitation in elderly patients with lumbar spinal stenosis - Yushan Guo; Xianghui Wang; Yingtao Shi (Frontiers in Medicine)
ObjectiveThis study sought to evaluate the impact of integrating rehabilitation gymnastics with compression therapy on postoperative recovery outcomes in elderly patients undergoing surgery for lumbar spinal stenosis.MethodsPatients aged ≥65 years hospitalized for lumbar spinal stenosis between July 2016 and July 2018 were included. Eighty-four patients receiving postoperative rehabilitation gymnastics and compression therapy were assigned to the intervention group, while 84 matched controls received standard care alone. Both groups underwent routine postoperative management. Clinical outcomes were assessed at 2 weeks, 1 month, and 3 months post-surgery using measures including lower-extremity deep venous thrombosis (DVT) incidence, visual analog scale (VAS) pain scores, Oswestry Disability Index (ODI), Japanese Orthopaedic Association (JOA) scores, and patient satisfaction rates.ResultsThe intervention group demonstrated significantly reduced DVT incidence, lower VAS and ODI scores, and higher JOA scores and satisfaction rates at 2 weeks and 1 month post-surgery compared to controls (all p < 0.05). By the third month, however, no statistically significant differences were observed between the groups.ConclusionCombining rehabilitation gymnastics with compression therapy enhances early postoperative recovery and functional outcomes in elderly lumbar spinal stenosis patients, though these benefits diminish by 3 months. These findings highlight the short-term efficacy of integrated rehabilitation strategies in accelerating postoperative healing.